Physical fitness and risk of myocardial infarction in Copenhagen males aged 40-59: a five- and seven-year follow-up study. - Gyntelberg, Finn; Lauridsen, Lone; Schubell, Ken (Scandinavian Journal of Work, Environment & Health, 1980)
Physical fitness and risk of myocardial infarction in Copenhagen males aged 40--59: a five- and seven-year follow-up study. Scand j work environ health 6 (1980) 170--178. A 5-a follow-up study on 5,249 Copenhagen males showed that the incidence of myocardial infarction was related to the level of physical fitness at the time of entry into the study, as determined by the indirect measurement of maximal oxygen uptake. Men having a physical fitness level within the lowest fifth of the total sample has a three times higher incidence of myocardial infarction than men in the upper two-fifths. This increased risk was independent of smoking habits and serum cholesterol level but may be partly or entirely dependent on blood pressure levels, as shown by use of a multiple logistic regression analysis. The men with the heaviest occupational physical activity had a somewhat higher risk of myocardial infarction than men with sedentary jobs. The data on leisure-time physical activity and risk of coronary heart disease indicated that only physical activity inducing a physical training effect is related to decreased risk.
Keywords: bicycling; coronary heart disease; follow-up study; leisure-time physical activity; male; man; myocardial infarction; occupational physical activity; physical fitness; risk